Simultaneous saccharification and viscosity reduction of cassava pulp using a multi-component starch- and cell-wall degrading enzyme for bioethanol production - Poonsrisawat, Aphisit (3 Biotech, 2017)
In this study, an efficient ethanol production process using simultaneous saccharification and viscosity reduction of raw cassava pulp with no prior high temperature pre-gelatinization/liquefaction step was developed using a crude starch- and cell wall-degrading enzyme preparation from Aspergillus aculeatus BCC17849. Proteomic analysis revealed that the enzyme comprised a complex mixture of endo- and exo-acting amylases, cellulases, xylanases, and pectina ses belonging to various glycosyl hydrolase families. Enzymatic hydrolysis efficiency was dependent on the initial solid loading in the reaction. Reduction in mixture viscosity was observed with a rapid decrease in complex viscosity from 3785 to 0.45 Pa s with the enzyme dosage of 2.19 mg/g on a dried weight basis within the first 2 h, which resulted from partial destruction of the plant cell wall fiber and degradation of the released starch granules by the enzymes as shown by scanning electron microscopy. Saccharification of cassava pulp at an initial solid of 16% (w/v) in a bench-scale bioreactor resulted in 736.4 mg glucose/g, which is equivalent to 82.92% glucose yield based on the total starch and glucan in the substrate, after 96 h at 40 °C. Simultaneous saccharification and fermentation of cassava pulp by Saccharomyces cerevisiae with the uncooked enzymatic process led to a final ethanol concentration of 6.98% w/v, equivalent to 96.7% theoretical yield based on the total starch and cellulose content. The results demonstrated potential of the enzyme for low-energy processing of cassava pulp in biofuel industry.